SCREENING INSTRUMENT FOR ZAKAH CAPITAL ASSISTANCE EGIBILITY - Harun, Noor Fazni; Ab Rahman, Asmak (Jurnal Syariah, 2023)
This study aims to determine the need for a viable and comprehensive screening instrument for selecting those individuals eligible for receiving financial assistance from zakah institutions in Malaysia. The study uses qualitative research methods and collects primary data with the help of semi-structured interviews with five zakah institutions in Malaysia. Complete consensus was found among all respondents on the need for a viable and comprehensive instrument to screen prospective zakah business recipients. The screening instrument will facilitate the evaluation process to determine eligibility on the basis of pre-formulated criteria and minimize manipulation and fraud. The study recommends that zakah authorities should have a screening instrument to select zakah recipients eligible for capital assistance.